A rare case of familial reactive perforating collagenosis - Anup Kumar Tiwary; Dharmendra Kumar Mishra; Shyam Sundar Chaudhary (Our Dermatology Online, 2017)
Reactive perforating collagenosis is a rare disorder of transepidermal elimination in which genetically altered collagen is extruded out through the epidermis. This disease usually starts as asymptomatic or pruritic umbilicated papules on extensor aspects of extremities and face, and the lesions become more conspicuous with age. It has two forms acquired and inherited form, of which inherited form is extremely rare. Here, we document a case of inherited form of reactive perforating collagenosis in a 13 year old boy having multiple asymptomatic hyperpigmented umbilicated papules with a central keratotic plug distributed chiefly over face and extensor aspect of upper and lower extremities since his infancy, with history of similar lesions in his 18 year old elder brother.